GUIDANCE COUNSELING MANAGEMENT IN ANTICIPATION OF BULLYING AT INTEGRATED ISLAMIC JUNIOR HIGH SCHOOL AD DURRAH MEDAN - Munawwarah, Tarisa; Wijaya, Candra (Benchmarking: Jurnal Manajemen Pendidikan Islam, 2025)
Bullying is a common problem in schools and has a negative impact on student development. The existence of counseling management plays a crucial role in preventing and addressing all forms of bullying that occur within the school environment. This study aims to describe and analyze the implementation of counseling management in anticipating bullying at SMP Islam Terpadu Ad Durrah Medan. The method used is descriptive qualitative with data collection through interviews, observations, and documentation. The research findings show that counseling management is carried out in a structured manner through three main stages: planning, implementation, and evaluation. In the planning stage, an Anti-Bullying Team is formed to develop a program based on student needs assessment. The implementation stage includes the BK Me Time program, Islamic Personal Development, anti-bullying counseling, as well as individual, group, and class counseling services. Evaluation begins with two main stages: first, periodic evaluations conducted each time there is a meeting with the counseling teacher, principal, and student affairs department. Second, an evaluation at the end of the academic year, which aims to assess the final results, including the program's impact on bullying issues and identify necessary improvements for the following academic year.